PENGGUNAAN MEDIA PEMBELAJARAN DIGITAL DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA - Abdul Faris; Suprapti; Nurul Inayati; Adwia; Niswatun Hasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the massive development of inFormation and communication technology (ICT), which demands a shift in the education paradigm towards a student-centered model. Digital learning media has become a vital component to overcome monotonous conventional learning, but the main challenge is sustaining student learning motivation. Motivation is a critical key that influences engagement , persistence, and academic outcomes. Therefore, this study aims to conduct a Systematic Literature Review (SLR) to synthesize empirical findings regarding the effectiveness and implementation of digital learning media on student learning motivation.The methodology used is the Systematic Literature Review (SLR), involving the identification, evaluation, and critical analysis of primary studies published within the period of 2020 to 2025. The literature search was conducted through major academic databases (Google Scholar, Scopus, and ERIC) based on predetermined inclusion criteria and search strings. The research stages included determining research questions, article selection, data extraction, and thematic synthesis. The results and discussion indicate that digital learning media has high effectiveness in enhancing student learning motivation due to its interactive, visual, and personal nature. The most dominant types of media used are gamification (such as Quizizz, Kahoot!) and interactive videos. Nevertheless, the implementation still faces major constraints, namely technological infrastructure limitations, insufficient teacher training in digital literacy, and the issue of digital fatigue among students. The conclusion of this study provides comprehensive insights for educators and curriculum developers regarding optimal strategies for leveraging technology to support adaptive learning motivation in the digital age.